Évoquer la mémoire politique dans un contexte autoritaire : « l’extrême gauche » tunisienne entre mémoire du passé et identité présente - Larbi Chouikha (L’Année du Maghreb)
Even today, evocation of the political memory of activists of the “far left” imprisoned and tortured under Bourguiba remains problematic. Indeed, the authoritarian regime persists in monopolizing the political experience of the past by monitoring its effects, channeling revisionist initiatives and imposing its vision of reconciliation. At the same time, the memory of such events for former political prisoners may appear incomplete so long as the project that underlay their political activism is not longer vindicated and the groups with which they identified disbanded. Notwithstanding the difficult circumstances of public debate, the discussion of these years occasionally resurfaces in connection with events.